Streamlining Operational Efficiency Through Inter-organizational Business Network in Beijing, China - Chen, Ying (Pacific International Journal, 2025)
This study investigates the relationship between inter-organizational business networks and operational efficiency among 300 employees across various industries in Beijing, China. Using a quantitative comparative correlational design, the research revealed high implementation levels of inter-organizational networks in risk management with a mean of 2.89, advocacy at 2.89, innovation at 2.90, and flexibility at 2.74. Operational efficiency demonstrated strong performance in production with a mean of 3.12 and supply chain management at 3.08, while inventory management scored lower at 2.73. Demographic analysis showed employees with 5-10 years of service perceived network effectiveness 15% higher than newer colleagues, and female respondents reported 8% greater satisfaction with collaborative advocacy. The study identified three key mechanisms connecting networks to efficiency: resource sharing with a beta of 0.42, knowledge transfer at 0.38, and joint problem-solving at 0.35. These findings indicate that while inter-organizational networks significantly enhance operational performance, their impact varies across business functions and employee demographics. The research proposes a strategic implementation plan featuring inventory optimization software, supply chain visibility platforms, and cross-functional advocacy teams, with an estimated budget of 900,000 yuan to maximize network benefits.